An automated real‐time PCR assay for synovial fluid improves the preoperative etiological diagnosis of periprosthetic joint infection and septic arthritis. Issue 2 (29th December 2020) - Yang, Fan; Choe, Hyonmin; Kobayashi, Naomi; Tezuka, Taro; Oba, Masatoshi; Miyamae, Yushi; Morita, Akira; Abe, Koki; Inaba, Yutaka
Abstract: Synovial fluid is important for the preoperative etiological diagnosis of suspected periprosthetic joint infection (PJI) or septic arthritis (SA). GENECUBE, an automated real‐time polymerase chain reaction (PCR) assay, was used to detect bacterial mecA (methicillin resistance) and was compared with microbiological cultures for preoperatively diagnosing PJI and SA in 74 patients suspected of these infections and thus earmarked for surgery. PJI and SA were diagnosed in 21 and 6 cases, respectively, using modified ICM 2018 diagnostic criteria. Microbiological cultures determined methicillin‐resistant staphylococcus (MRS) as the causative organism in six samples, which were all positive in the GENECUBE assay. Significantly also, the GENECUBE assay detected six MRS infections in culture‐negative but infection‐diagnosed patients, and in one inconclusive case, suggesting a higher sensitivity of this assay. Compared with microbiological culture, the sensitivity and specificity of the GENECUBE assay for mecA was 100% and 92.2%, respectively. However, GENECUBE also produced invalid results in three cases, suggesting possible PCR inhibitors in the synovial fluid samples. We additionally validated the accuracy of pan‐bacterial real‐time PCR targeting 16S rRNA and other tests. Pan‐bacterial real‐time PCR was as effective as preoperative bacterial culture testing, although the α‐defensin assay had the highest sensitivity at 100%. Hence, fully automated real‐time PCR targeting of the bacterial mecA gene improves the etiological diagnosis of PJI and SA by reducing the testing time and lowering the false‐positive detection rates. A screening approach for α‐defensin followed by bacterial mecA gene testing in synovial fluids is therefore a more efficient method of preoperatively diagnosing PJI and SA.